Cassia surattensis: An Indispensable Source for Natural Antioxidants - Fatima, Ambreen; Riaz, Tauheeda; Abbas, Nadia; Athar Abbasi, Muhammad; Zahra Siddiqui, Sabahat; Khan, Zaheer-ud-Din; Rehman, Aziz-ur (Asian Journal of Chemistry, 2012)
In this study, phytochemical screening and antioxidant capacity of aqueous and organic fractions of aerial parts of Cassia surattensis L. was investigated. Phytochemical tests showed that many secondary metabolites including flavonides, steroids, alkaloids, saponins, tannins and anthraquinones etc., were present in the different plant extracts like crude methanolic extract, n-hexane, chloroform, ethyl acetate, n-butanol soluble fractions and remaining water fraction. First of all the antioxidant components were extracted in methanol and then partitioning was done in solvents of different polarity. Evaluation of the antioxidant activity and radical scavenging activity of these fractions was done by using different antioxidant assays such as total phenolic contents (TPC), 2,2-diphenyl-1-picrylhydrazil (DPPH) scavenging and the trolox equivalent antioxidant capacity (TEAC) of all the studied fractions was evaluated by FRAP and ABTS (radical cation scavenging activity). All the fractions exhibited significant antioxidant potential. The results showed that highest % inhibition of DPPH was shown by ethyl acetate soluble fraction with IC50 4.00 ± 1.7 μg/mL of butylated hydroxytoluene (BHT) equivalents. This fraction also contained highest total phenolic contents (348.83 ± 1.5 mg of gallic acid equivalents) and highest TEAC value (0.99 ± 0.9) measured by ABTS assay and methanolic crude extract exhibited highest total TEAC value (158.5 ± 1.2) by FRAP method.